The Real-World Effectiveness of Human Immunodeficiency Virus Pre-Exposure Prophylaxis in Adults in Alberta, Canada: A Retrospective Population-Based Cohort Study - Elissa Rennert May; Mu Lin; Shannon L. Turvey; Derek S. Chew; Marcello Tonelli; Scott Klarenbach; Neesh Pannu; Emily Christie; Stephanie Thompson; Aminu Bello; Darren Lau; Caley B. Shukalek; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Conclusion: HIV PrEP appears to be effective for preventing HIV infection in this real-world population-based study in Alberta, Canada. Strategies to mitigate residual HIV risk in PrEP users are needed.